"Nothing about us without us": navigating engagement as hearing researcher in the Deaf community. Issue 4 (2nd October 2018) - Ferndale, Danielle
ABSTRACT: The Deaf context presents unique challenges to the concept of engaged research. Language and cultural differences, as well as contemporary academic pressures, often inform researcher choices rather than addressing social change with the people and community/ies facing the issues. In this article, I reflect on my experiences of producing and disseminating engaged research with Deaf people in a contemporary academic context. Hearing researchers frequently conduct research with/on people with whom they do not share an embodied experience, language, and culture in an academic system that is more often than not inaccessible (linguistically, educationally, financially, culturally) to Deaf people. The inaccessibility of academia also points to a history of hearing society perpetrating oppressive acts on the Deaf communities of the world. This history continues to shape Deaf/hearing relations today; therefore, I discuss the ethics, politics, and practicalities of doing engaged research as a hearing researcher with Deaf people.